PENGARUH SERVANT LEADERSHIP DENGAN BUDAYA ORGANISASI SEBAGAI MEDIASI TERHADAP KINERJA TENAGA PENDIDIK PADA LEMBAGA PENDIDIKAN KRISTEN DAN KATOLIK DI SURABAYA - Wulandari, Trifena; Lindawati, Tuty; Pradana, Dominicus Wahyu (Universitas Katolik Widya Mandala Surabaya, 2021)
The purpose of this research was to analyze and test the effect of servant leadershipwith organizational culture as mediation for performance educators in Christianand Catholic education institution in Surabaya. This research wrote by Kurniawan(2019) and Sihombing, et al (2018) who analysed the influence of servant leadersipand organization culture for performance as basis of this research. This researchpicked 100 respondents as sample from education woker at Christian or Catholiceducation institution in Surabaya.The measurement tool of this research is questionnaire. Data obtained and processedwith Partial Least Square analytical technique by SmartPLS 3.0 program. The result of this research proved that servant leadership has positive and significant influence for organization culture also its performance, and organization culture hasno influence for performance.